Implementation of Discovery Learning Model to Improve Student Learning Outcomes in Fiqh Learning at MI Al-Fatah Manggarai Barat - Mulyadi, Musni; Zubaedi, Muhammad (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve learning outcomes in the subject of Fiqh with the Discovery Learning Learning Model for fourth grade students at MI Al-Fatah Manggarai Barat in 2024, this type of research uses Classroom Action Research, consisting of four stages, namely; planning, action, observation, reflection. The subjects of the study were 20 fourth grade students at MI Al-Fatah Manggarai Barat. The data collection method used observation, documentation, testing and interview methods. The results of this study showed a significant increase in students' critical and collaborative thinking. The percentage of students' critical thinking in the pre-cycle was 48%, cycle I was 65%, Cycle II meeting I increased to 85%, Cycle III increased to 95%. Student learning outcomes obtained in cycle I were 84.55%, but in cycle II it became 89.25%, Cycle III the application of Discovery Learning was increased again so that the percentage obtained increased to 97.55%. The application of the Discovery Learning model can improve Learning Outcomes by making modifications in terms of; use of interesting media, seating arrangements, and effective classroom management strategies.